Production of fungal pectinase enzyme through solid substrate fermentation of estate waste for improvement of enzymatic oxidation and increasing the quality of CTC tea - Tri Panji; Suharyanto Suharyanto; Shabri Shabri; Dadan Rohdiana; Yusianto Yusianto (Research Institute for Tea and Cinchona, 2015)
Enzymes, especially pectinase, plays an important role in the processing of tea that determines the quality and the color appearance of black tea. The main obstacle encountered in the application of enzymes in food processing in general, and in particular in the processing of black tea is the price of commercial enzyme that are still very expensive, because it is still imported. Indonesia has a high fungal diversitythat is potential as producer of commercial pectinase enzyme. To reduce the cost of production, fermentation was done using solid waste of plantation that rich of pectin content such as cocoa pod husk that has not been optimally utilized. The research aimed to develop the production technology for pectinase enzymes of fungi through solid substrate fermentation for applications in the processing of CTC black tea. Research includes the isolation and selection of local superior fungi producing enzymes pectinase, optimization of enzyme production by fungi isolates were selected through a solid substrate fermentation using cocoa pod husk waste, production optimization included optimization of fermentation time and substrate composition, enzyme extraction of fermented substrate, and application of pectinase enzyme extracts in the processing of CTC black tea and sensory test of fermented tea. The results showed that it has been obtained isolates of Aspergillus niger on Pectinase Screening Agar Medium (PSAM) which was capable of producing pectinase enzyme on growing media of mix cocoa pod husk and rice bran with additional of enrichment media. The optimum conditions of pectinase production was obtained in the composition of cacao pod husk: rice bran (80:20 w/w) plus enrichment media, the incubation time of 9 days, which produced pectinase activity of 125 U/mL. Applications of pectinase on enzymatic oxidation of CTC tea proved that it was capable of raising the quality of the tea flavor, though the tea gradedid not change.